2012
DOI: 10.1002/anie.201204842
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Alkaline Hydrogen Evolution Reaction Activity through the Bifunctionality of Ni(OH)2/Metal Catalysts

Abstract: Active in alkaline environment: The activity of nickel, silver, and copper catalysts for the electrochemical transformation of water to molecular hydrogen in alkaline solutions was enhanced by modification of the metal surfaces by Ni(OH)(2) (see picture; I = current density and η = overpotential). The hydrogen evolution reaction rate on a Ni electrode modified by Ni(OH)(2) nanoclusters is about four times higher than on a bare Ni surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
417
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 669 publications
(445 citation statements)
references
References 27 publications
12
417
2
1
Order By: Relevance
“…It has been experimentally proved by developing hybrid catalyst that has an active component for water dissociation. It is found that incorporation of water active catalyst can increase the HER activity of its counterpart (HER active catalyst) 22. For example Markovic group has developed the Ni(OH) 2 decorated Pt catalyst to improve the HER activity of Pt by lowering the energy barriers for water dissociation as shown in Figure 1 13.…”
Section: Challenges Associated With Her In Alkaline Mediummentioning
confidence: 99%
See 4 more Smart Citations
“…It has been experimentally proved by developing hybrid catalyst that has an active component for water dissociation. It is found that incorporation of water active catalyst can increase the HER activity of its counterpart (HER active catalyst) 22. For example Markovic group has developed the Ni(OH) 2 decorated Pt catalyst to improve the HER activity of Pt by lowering the energy barriers for water dissociation as shown in Figure 1 13.…”
Section: Challenges Associated With Her In Alkaline Mediummentioning
confidence: 99%
“…A water dissociation happens at the edges of Ni(OH) 2 clusters and produces the hydrogen intermediates that adsorb on the surface of neighboring Pt active sites and recombine to yield molecular hydrogen. To further confirm the requirement of high energy for additional water dissociation step and eliminate the confusion of Pt, hybrid catalysts based on cost‐effective metals, e.g., Ni, Cu, Ag have been designed and found that after surface modifications by Ni(OH) 2 the performance of these metals also approach to their activity in acidic medium 22. Although this method has enhanced the activity of PGMs and cost effective metals in alkaline medium but have several reservation for practical applications likewise complex synthesis methods, hard to control the interface and stability concerns on longer use.…”
Section: Challenges Associated With Her In Alkaline Mediummentioning
confidence: 99%
See 3 more Smart Citations